Some Coefficient Inequalities of q-Starlike Functions Associated with Conic Domain Defined by q-Derivative. (8th October 2018) - Mahmood, Shahid; Jabeen, Mehwish; Malik, Sarfraz Nawaz; Srivastava, H. M.; Manzoor, Rabbiya; Riaz, S. M. Jawwad
Abstract : This article deals with q-starlike functions associated with conic domains, defined by Janowski functions. It generalizes the recent study of q-starlike functions while associating it with the conic domains. Certain renowned coefficient inequalities in connection with the previously known ones have been included in this work.